Persepsi Kegunaan, Kemudahan, Keamanan dan Kerahasiaan, Serta Kepuasan Wajib Pajak Pengguna E-Filing dan Non E-Filing untuk Pajak Tahunan Orang Pribadi - Ria Adhi Pramesti; Sukirman Sukirman; Icuk Rangga Bawono (Program Studi Ekonomi Islam, Fakultas Ekonomi dan Bisnis - Universitas Syiah Kuala, 2021)
This study aimed to compare the perceived usefulness, perceived convenience, perceived security and perceived satisfaction of tax payers between users of e-filing and non e-filing. The research located in Tax Office (KPP) Pratama Purwokerto, using primary data and secondary data collected by survey method. The registered taxpayers to use e-filing are 17.831 and the non e-filing are 44.332. Paired t-test was used to compare each variable between users of e-filing and non e-filing. Based on the analysis, it is can be concluded that: (1) there is no difference in perceived usefulness, users of e-filing and non e-filing has the perception that reporting tax return online and manual are equally useful; (2) there is a difference in perceived convenience, the user has a perception that the use of e-filing is more convenience than the manual; (3) there is a difference in perceived security, the user has a perception that the use of e-filing is more secure and confidential than the manual; (4) there is no difference in perceived satisfaction, either the e-filing and non e-filing are equally satisfied; and (5) as a whole, there are differences of perception between users of e-filing and non e-filing, so it can be concluded that the benefits of the usefulness of e-filing is influenced by variables of usability, convenience, security, confidentiality and satisfaction of taxpayers on e-filing.